Limitations of satellite precipitation products in capturing extreme precipitation events: An object-based evaluation over China - Hongji Gu; Dingtao Shen; Jinming Chen; Chunxiao Zhang; Shuting Xiao; Fei Yu (Atmospheric Research, 2026)

Serine metabolism hijacks radiotherapy-driven antitumor immunity via suppressing STING-dependent DNA sensing - Xiaochuan Hong; Yuanqin Yang; Lingling Wu; Shuting Xu; Chao Yang; Tong Cui; Qishan Wang; Zhihao Wu; Xueni Yu; Qi Chen; Hanyu Hong; Qianjiang Chen; et al. (Science Bulletin, 2026)

Myasthenia Gravis patients have reduced DTI-ALPS-Index and gBOLD-CSF coupling, suggesting impaired brain waste clearance - Jianxian Zeng; Shuting Han; Mengying Zhu; Yi Shang; Peng Wu; Qinghua Gu; Yonggang Li (Brain Imaging and Behavior, 2026)

Unbiased Segmentation and Multifeature Classification of Cortical Neuronal Activity Reveals Complex Dynamics Under Anesthesia - Zilin Wang; Ao Li; Guihua Xiao; Xingzheng Gu; Zhilei Wang; Shuting Guo; Rujin Zhang; Chaowei Zhuang; Jiangbei Cao (Neuroscience Bulletin, 2026)
Cortical layer 2/3 plays a pivotal role in regulating perception and consciousness. However, the effects of anesthetic agents on the dynamic activity patterns in this layer remain poorly understood. This study examined how neuronal activity in cortical layer 2/3 dynamically changes under anesthesia. Using high-resolution wide-field microscopy, we performed whole-brain synchronous imaging of layer 2/3 neuronal activity in mice. Using these recordings, we performed an unbiased segmentation of the awake, anesthesia, and recovery stages and classified neurons into three categories according to their activity features. Our findings revealed the characteristics of cortical dynamics under anesthesia, including a rebound effect during recovery and nonlinear changes in neuronal activity. We also confirmed the consistent and uniform characteristics of superficial cortical layer activity under anesthesia. These results increase the understanding of cortical dynamics and provide a theoretical basis for improving clinical monitoring techniques and protocols.

Correlation analysis of monosaccharide composition and in vitro antioxidant and hypoglycemic activities of Tremella fuciformis spore polysaccharides - Jianqiu Chen; Xiaoyu He; Shuting Zhou; Yujie Chen; Chunyuan Kong; Yating Deng; Shikai Ruan; Chengzhen Gu; Shujing Sun (Food Chemistry, 2026)

FAK mediates mechanical signaling to maintain epithelial homeostasis through YAP/TAZ-TEADs - Yang Peng; Qiuyun Yuan; Shuting Zhou; Jianguo Gan; Zhengzhong Shen; Xiaoqiang Xia; Yuchen Jiang; Qianming Chen; Yao Yuan; Gu He; Qiang Wei; Xiaodong Feng (Histochemistry and Cell Biology, 2025)

Integrated metabolomics and transcriptomics reveal the nutritional profiles and molecular mechanisms in colored cauliflowers - Xiaoguang Sheng; Mengfei Song; Jiansheng Wang; Huifang Yu; Yusen Shen; Shuting Qiao; Fan Lin; Sifan Du; Honghui Gu (Food Bioscience, 2025)

Formation of highly toxic p-benzoquinones byproducts during ozonation of cresols - Weixu Tang; Jianjian Wei; Shuting Wang; Qiang Cheng; Aroob Abid; Jia Gu; Min Zheng; Dehua Ma (Journal of Environmental Sciences, 2025)

Mitigating impacts of hot weather on outdoor workers by attaching phase change materials based on body mapping of physiology - Shuting Gu; Zhen Yang; Hongyu Chen; Wenwei Ma; Hongyi Gao; Ying Zhang; Jingxian Xu (Building and Environment, 2025)

Identification and characterization of terpene synthase genes accounting for volatile terpene emissions in the flower of Paeonia lactiflora - Qian Zhao; Yuqing Li; Lina Gu; Shuting Li; Di He; Shanrong Dong; Qingyu Zhang; Jianrang Luo; Yanlong Zhang (Postharvest Biology and Technology, 2025)

Energy, environmental footprints and economic benefit of substituting inorganic fertilizer with organic manure for winter wheat in Huanghuaihai Plain - Lei Wang; Jianjie Bi; Jing Chen; Baizhao Ren; Bin Zhao; Peng Liu; Shubo Gu; Shuting Dong; Jiwang Zhang (European Journal of Agronomy, 2025)

Fine mapping of a major co-localized QTL associated with self-incompatibility identified in two F2 populations (broccoli × cauliflower and cauliflower × Chinese kale) - Yusen Shen; Jiansheng Wang; Xiaoguang Sheng; Huifang Yu; Ranjan K. Shaw; Mengfei Song; Shiyi Cai; Shuting Qiao; Fan Lin; Honghui Gu (Theoretical and Applied Genetics, 2024)

Controllable preparation of graphene glass fiber fabric towards mass production and its application in self-adaptive thermal management - Ruojuan Liu; Fan Yang; Shuting Cheng; Xianghe Yue; Fushun Liang; Wenjuan Li; Jingnan Wang; Qinchi Zhang; Liangyu Zou; Hao Yuan; Yuyao Yang; Kangyi Zheng; et al. (Science Bulletin, 2024)

Efficient electrocatalytic OOH production on P–N–CuO for selective cleavage of lignin C–C bonds in the photoelectric collaborative system - Linglong Shi; Huifang Ma; Bin Shan; Da Li; Shuangzhen Guo; Yu Liu; Jianjie Wang; Weifang Dong; Mengqi Li; Shuting Gu; Weiyu Xia (Chemical Engineering Journal, 2024)

Roles of alcohol group in functionalized carbon nitride for photocatalytic oxidation - Shuting Feng; Xincheng Li; Xianmo Gu; Ruiyi Wang; Yunwei Wang; Zhanfeng Zheng (Fuel, 2024)

Lypd1-DTR/+: A New Mouse Model for Specifically Damaging the Type Ic Spiral Ganglion Neurons of the Cochlea - Di Zhang; Minhui Ren; ZhengHong Bi; Yunpeng Gu; Shuting Li; Guangqin Wang; Xiang Li; Zhiyong Liu (Neuroscience Bulletin, 2023)

Big-sized trees and higher species diversity improve water holding capacities of forests in northeast China - Yanbo Yang; Lixin Jing; Qi Li; Chentao Liang; Quanxing Dong; Shuting Zhao; Yuwen Chen; Danqi She; Xu Zhang; Lei Wang; Guanchao Cheng; Xiting Zhang; et al. (Science of The Total Environment, 2023)

From bench to bedside: targeting lymphocyte activation gene 3 as a therapeutic strategy for autoimmune diseases - Xueyin Zhou; Yiming Gu; Huihong Wang; Wei Zhou; Lei Zou; Shuting Li; Chunyan Hua; Sheng Gao (Inflammation Research, 2023)

Discerning drivers and future reduction paths of energy-related CO2 emissions in China: combining EKC with three-layer LMDI - Qunli Wu; Shuting Gu (Environmental Science and Pollution Research, 2021)